2011
DOI: 10.1016/j.micromeso.2010.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Reverse shape selectivity in the adsorption of hexane and xylene isomers in MOF UiO-66

Abstract: a b s t r a c tAn adsorption study of hexane and xylene isomers mixtures was addressed in a rigid zirconium terephthalate UiO-66 (UiO for University of Oslo) with octahedral and tetrahedral cavities of free diameter close to 1.1 nm and 0.8 nm, respectively. Multicomponent equimolar breakthrough experiments show that the adsorption hierarchy of structural isomers in UiO-66 is opposite to the one observed in conventional adsorbents. For hexane isomers, it was found that the amount adsorbed increases with the deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
231
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 273 publications
(254 citation statements)
references
References 24 publications
21
231
1
1
Order By: Relevance
“…This unusual reverse shape selectivity (nHEX is the less adsorbed component), previously reported by Barcia et al for the bared UiO-66 solid [14], is once again observed in all runs, evidencing that the functionalization of the ligand does not impact the sorption hierarchy of the hexane isomers. As explained the reverse shape selectivity seems to be related with the linear long nature of nHEX (1.03 Â 0.49 nm), which might be too long to be accommodated into the small tetrahedral cages ($8 Å; Fig.…”
Section: Screening Studies Of Hexane Isomers In Uio-66_brsupporting
confidence: 78%
See 2 more Smart Citations
“…This unusual reverse shape selectivity (nHEX is the less adsorbed component), previously reported by Barcia et al for the bared UiO-66 solid [14], is once again observed in all runs, evidencing that the functionalization of the ligand does not impact the sorption hierarchy of the hexane isomers. As explained the reverse shape selectivity seems to be related with the linear long nature of nHEX (1.03 Â 0.49 nm), which might be too long to be accommodated into the small tetrahedral cages ($8 Å; Fig.…”
Section: Screening Studies Of Hexane Isomers In Uio-66_brsupporting
confidence: 78%
“…Thus, we have recently reported the use of the highly stable (T $350-400°C or P $10,000 kg/cm 2 ) porous cubic zirconium terephthalate UiO-66 (UiO for University of Oslo; Zr 6 O 4 (OH) 4 (C 6 H 4 (CO 2 ) 2 ) 6 ÁnH 2 O) [13] for the separation of hexane isomers mixtures (n-hexane (nHEX), 3-methylpentane (3MP), 2,3-dimethylbutane (23DMB), 2,2dimethylbutane (22DMB)). Remarkably, UiO-66 which possesses an important porosity (S BET > 1100 m 2 /g) with tetrahedral ($8 Å) and octahedral cavities ($11 Å) accessible by microporous triangular windows (5-7 Å), exhibited an opposite sorption hierarchy (22DMB > 23DMB > 3MP > nHEX) to the one observed in conventional adsorbents [14], with selectivity values reaching four for the ratio 22DMB/ nHEX. This reverse shape selectivity might be attributed to the rotational freedom of the molecules within the small cages [14].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…50 The usual characterization experiments (XRPD, TGA, IR spectroscopy, and sorption analysis) were performed to confirm its purity.…”
Section: Synthesesmentioning
confidence: 99%
“…It is worth noting that modulators/additives have been formerly employed to synthesize various Zr-based MOFs. 39,41,44,46,50,[52][53][54][55][56][57][58][59][60][61][62][63][64] Compound 1, which has been synthesized recently 44 by the solvothermal reaction of ZrCl 4 , BDC-SO 3 Na and acetic acid in DMF, appeared to be unstable upon removal of guest molecules. In contrast, the reaction conditions presented here produced a highly crystalline solid that retained its crystallinity after removing the guest molecules from the pores.…”
Section: Syntheses and Activationmentioning
confidence: 99%